SOSIALISASI DAMPAK POSITIF DAN NEGATIF GAME ONLINE BAGI ANAK SEKOLAH DASAR - Andreas Andoyo; Agung Hening A (LP3K Lampung, 2021)
In this era of globalization, Gadjet may already be familiar to the public, this item may no longer be a luxury item or just a secondary need. Maybe in the millennial era like today, gadgets have become a basic need. The gadget is everyone's soulmate because the gadget has many functions, benefits, and various functions. One of the functions of the gadget is as entertainment, and the entertainment that is often used by the public is online games. In this era, who doesn't know online games? Online games are something that is not foreign to us. Because this online game is trending at the moment. You can play this online game either through a computer or smartphone. Now online games are not only played by parents but are now starting to be played by children and even worse, it has a bad impact on children. As for some of the bad effects of online games that are not yet known to many children, the PkM STMIK Pringsewu Team took the initiative to conduct knowledge dissemination to several schools to provide an understanding of the good and bad effects of these online games.